Penyelesaian perkara kumulasi isbat nikah dan cerai gugat menurut perspektif hukum islam di pengadilan agam panyabungan (Analisis Putusan No 502/Pdt.G/2024/PA.Pyb) - Amrar Mahfuzh Faza; Sangkot Rizky Azizah; Saidah Lubis; Ridwandi; Restu Lubis; A.Syarkawi Nasution; Riki Andi; Abdul Rahman (FKIP - Universitas Pahlawan Tuanku Tambusai, 2025)
Marriage according to the Compilation of Islamic Law (KHI) in article 2 is a very strong contract or mistsaqan ghalidzan to obey Allah's command and carry it out is worship. In Islamic law, marriage registration is not regulated, but the provisions of Law No. 1 of 1974 issued are a rule that must be obeyed by the Indonesian people, but not all people obey it. Therefore, to handle such problems, the Religious Court resolves the Marriage Isbat case. The Panyabungan Religious Court received a cumulative case, where the marriage isbat and divorce cases were combined and examined in one case. In decision No. 502 / Pdt.G / 2024 / PA.Pyb there are two cases that are combined in the cumulative case, namely marriage isbat and divorce lawsuit. The method used in this study is a qualitative method. This study analyzes the decisions in the Panyabungan Religious Court regarding the merger of marriage isbat and divorce lawsuit cases, in which the judge considered providing convenience or rukhsah.